Co-located wave-wind farms for improved O&M efficiency. (1st September 2018) - Astariz, S.; Vazquez, A.; Sánchez, M.; Carballo, R.; Iglesias, G.
Abstract: Co-located wave-wind farms enhance the competitiveness of marine energy in a number of ways, and in particular through their benefits in terms of Operation and Maintenance (O&M) – the subject of this work. The objective is to investigate how the reduction in significant wave height within a co-located farm caused by the extraction of wave power by the wave energy converters (WECs), also known as the shadow effect, results in enlarged weather windows for O&M tasks. This investigation is carried out through a case study of four wind farms in the North Sea, including a sensitivity analysis in terms of: (i) location (depth and distance from the coast), (ii) sea climate, and (iii) wind farm layout. Real (observed) sea conditions are considered, and a third-generation wave model (SWAN) is implemented on a high-resolution grid. It is found that the combination of wave and offshore wind energy increases the accessibility for O&M tasks over 13% in all the cases considered, leading to accessibility values of up to 82%. The best results are obtained for wind farms with square-like geometries, where the co-located WECs intercept both the prevailing and secondary wave directions, and with small spacings between converters. Besides, proximity to land is found to not be a favourable factor for exploiting this synergy between wave and offshore wind power. Highlights: The synergies between offshore wind and wave energy are discussed. The shadow effect of co-located WECs along the periphery of a wind farm is analysed. 4 operating offshore wind farms are considered as baseline scenarios. Conclusions about the influence of water depth, sea climate and layout are drawn.